An Analysis of Gucci Through Semiotic Roland Barthes - Luthfie Rizky Utama (MEDIOVA: Journal of Islamic Media Studies, 2022)
In the millennial era, people no see fashion as a primary commodity but they tend to improve social status. Citizens no longer concern with the originality. Therefore, influencers play a role in the formation of meaning through social media that is consumed by the public. This study aims to describe the signs in Gucci branding that represent social status. This study uses a interpretative qualitative method by observing and documenting the Gucci branding. This study uses semiotic theory of Roland Barthes. The results of this study find that there are 5 data which apply denotation, connotation, and myth to Gucci branding. Based on the data, it shows that there is a shift in signification in the Gucci branding which affects the meaning of the Gucci brand that it can increase a person's social status. Therefore, there is a relevance between Gucci branding and social status. The results of this study are expected to be an information in order to avoid information bias in the community.